Consumer Legal Protection Related to Goods Storage Agreements in Shopping Centers in Realizing Justice - Lira, M. Adnan; Buana, Andika Prawira; Wikra Wardhana Mamonto, Moch. Andry (Magister of Law, Faculty of Law, University of Mataram, 2024)
The development of shopping centers in Indonesia has increased the need for item storage services, but it has also raised legal issues related to consumer protection. This research aims to analyze the forms of legal protection for consumers regarding item storage agreements in shopping centers and identify efforts that can be made to achieve justice for consumers in this context. This study uses a normative legal research method with statutory and conceptual approaches. Data collection techniques are carried out through library research, while data analysis uses qualitative methods with deductive reasoning to interpret legal materials and formulate recommendations. The research results show that legal protection for consumers in item storage agreements in shopping centers is based on the Consumer Protection Act and the Civil Code, covering the guarantee of consumer rights, obligations of shopping centers, prohibition of detrimental standard clauses, compensation liability, reverse burden of proof principle, dispute resolution mechanisms, as well as supervision and law enforcement. To achieve justice for consumers, comprehensive efforts are needed including regulatory revision, increased supervision, consumer education, development of effective dispute resolution mechanisms, technology adoption, development of industry standards, increased transparency, development of special insurance products, periodic evaluations, strengthening the role of non-governmental consumer protection organizations, development of consumer rating systems, and improved coordination among relevant government agencies.